2009
DOI: 10.1111/j.1528-1167.2008.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a first acute symptomatic seizure epilepsy? Mortality and risk for recurrent seizure

Abstract: SUMMARYPurpose: To compare mortality and subsequent unprovoked seizure risk in a population-based study of acute symptomatic seizure and first unprovoked seizure due to static brain lesions. Methods: We ascertained all first episodes of acute symptomatic seizure and unprovoked seizure due to central nervous system (CNS) infection, stroke, and traumatic brain injury (TBI). Subjects were residents of Rochester, Minnesota, identified through the Rochester Epidemiology Project's records-linkage system between 1/1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
277
4
26

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(315 citation statements)
references
References 7 publications
8
277
4
26
Order By: Relevance
“…The prevalence of febrile seizures in this hospital‐based study was low, suggesting that many children with seizures are not admitted to the hospital. The seizures classified as acute symptomatic seizures may have been epileptic seizures 7. It is impossible to rule out residual confounding from factors not documented in this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The prevalence of febrile seizures in this hospital‐based study was low, suggesting that many children with seizures are not admitted to the hospital. The seizures classified as acute symptomatic seizures may have been epileptic seizures 7. It is impossible to rule out residual confounding from factors not documented in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies found increased risk for epilepsy but after seizures related to cerebrovascular disease7 and encephalitis 8. Additionally, early acute symptomatic seizures following trauma or ischemia increased the risk of subsequent epilepsy,9, 10 suggesting these acute seizures may be a marker of persistent susceptibility to repetitive unprovoked seizures, that is, epilepsy.…”
mentioning
confidence: 99%
“…симп томатические судороги, или судорожный синдром, являются одним из наиболее частых и грозных проявлений нейроинфекций, осложня-ющих течение заболевания и повышающих веро-ятность развития симптоматической эпилепсии [3][4][5][6]. К ним относятся пароксизмы, возникаю-щие в прямой временной связи с заболеванием.…”
unclassified
“…К ним относятся пароксизмы, возникаю-щие в прямой временной связи с заболеванием. Острые симптоматические судороги могут быть как однократными, так и повторными, в течение 7 суток и более [4,5]. В их основе лежит пораже-ние нейронов вследствие прямого цитопатоген-ного действия инфекционного агента либо опос-редованно через сосудистые или аутоиммунные механизмы [6].…”
unclassified
“…21 While children are rarely affected by ischemic, embolic, or hemorrhagic stroke, up to two-thirds of patients who experience perinatal infarction will eventually develop epilepsy, and in 25% of these cases, the seizures will be medically intractable. 13,16,25 Epilepsy surgery in children is safe and effective and can provide substantive gains in quality of life and developmental milestones, 15,36 but in general, it remains an underutilized treatment modality for multiple reasons, including but not limited to historical prejudice, practitioner bias, and parental concern over loss of functional capability.…”
mentioning
confidence: 99%